Determinants of inflation in Europe: A dynamic panel analysis - Lejla Čaklovica; Adnan S. Efendic (Financial Internet Quarterly, 2020)
This article offers an empirical analysis of determinants of inflation in 28 European economies that belonged to the transition group of countries in the end of the last century. We rely on dynamic panel methodology and find that economic and structural variables, including economic openness, unemployment, real wages, institutional effects, as well as external factors, such as prices of food and oil, determine the short-run inflationary dynamics in these countries. The obtained results also indicate that inflation rate is autoregressive in the observed period (2005-2015), confirming that contemporaneous inflation rate is determined by the entire history of these determinants. Our further investigation reveals long- term effects of the majority of these variables on price dynamics. Interestingly, distinction between the current EU and transition countries in the model does not lead to different conclusions.
Keywords: E3; E31; E50; 330; determinants of inflation; transition countries; dynamic panel model